2008
DOI: 10.1093/nar/gkn498
|View full text |Cite
|
Sign up to set email alerts
|

The Bloom's syndrome helicase (BLM) interacts physically and functionally with p12, the smallest subunit of human DNA polymerase δ

Abstract: Bloom's syndrome (BS) is a cancer predisposition disorder caused by mutation of the BLM gene, encoding a member of the RecQ helicase family. Although the phenotype of BS cells is suggestive of a role for BLM in repair of stalled or damaged replication forks, thus far there has been no direct evidence that BLM associates with any of the three human replicative DNA polymerases. Here, we show that BLM interacts specifically in vitro and in vivo with p12, the smallest subunit of human POL δ (hPOL δ). The hPOL δ en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 47 publications
(63 reference statements)
0
18
0
Order By: Relevance
“…Later studies using fiber tracking analysis confirmed that defects in BLM or WRN decrease the rate of replication fork progression (196, 197). One explanation for this observation is that WRN and BLM resolve or remove DNA structures that impede fork movement (60, 104, 198), such as hairpins and G4 DNA (199, 200). Slower fork movement has also been observed in RECQL1-deficient (but not RECQL4-deficient) cells (38).…”
Section: Recq Helicases In Dna Replicationmentioning
confidence: 99%
“…Later studies using fiber tracking analysis confirmed that defects in BLM or WRN decrease the rate of replication fork progression (196, 197). One explanation for this observation is that WRN and BLM resolve or remove DNA structures that impede fork movement (60, 104, 198), such as hairpins and G4 DNA (199, 200). Slower fork movement has also been observed in RECQL1-deficient (but not RECQL4-deficient) cells (38).…”
Section: Recq Helicases In Dna Replicationmentioning
confidence: 99%
“…Similarly, other proteins, yet to be identified, may interact with the large oligomeric complexes with higher affinity and in this way promote the other specialized enzymatic activities of these helicases. A challenging avenue for future studies will be to apply the biochemical and biophysical approaches described above to test if newly discovered RecQ helicase binding proteins regulate the different enzymatic activities of these enzymes by specifically interacting with one or other oligomeric forms (Aygun et al, 2008;Selak et al, 2008;Singh et al, 2008;Xu et al, 2008). One candidate in the case of BLM is the RMI1/RMI2 complex that, like RPA, is a multi-OB-fold containing a complex that is capable of stimulating BLM to disrupt Holliday junctions (Raynard et al, 2006;Wu et al, 2006).…”
Section: Different Oligomeric States Of Recq Helicasesmentioning
confidence: 99%
“…BLM interacts with and stimulates the enzymatic activities of DNA polymerase ␦ and FEN1 endonuclease, both of which are components of the replication machinery (43,44,51). BS cells exhibit a reduced replication fork rate and an increased frequency of fork pausing (36), suggesting that BLM participates in normal replication progression.…”
mentioning
confidence: 99%